Mathematical model of asynchronous motor diagnosis - Курашкин, Сергей Федорович; Курашкін, Сергій Федорович; Kurashkin, Serhii; Попова, Ірина Олексіївна; Попова, Ирина Алексеевна; Popova, Iryna; Попрядухін, Вадим Сергійович; Попрядухин, Вадим Сергеевич; Popriadukhin, Vadym; Ковальов, Олександр Вікторович; Ковалев, Александр Викторович; Kovalov, Oleksandr (My University, 2019)
Increased thermal deterioration of an asynchronous motor insulation is one of the reasons that affect its reliability. Thermal overloads occur due to a number of factors leading to an excess of the rated current. Among them, the most significant are asymmetrical supply voltage, phase failure, short circuits in power lines. Thermal deterioration of motor insulation is influenced by the ambient temperature, the loading ratio, which may differ from the nominal values, both in the smaller and in the larger direction. This leads to under-utilization of the insulation resource consumption or, on the contrary, to increased consumption. The task of diagnosis is to limit the operation of the electric motor, the thermal deterioration of the insulation keeps within the limits limited by the manufacturer, in spite of electric motor operation mode.
Keywords: insulation; reliability; factors; short circuits; consumption; diagnosis